Geological interpretation of magnetotelluric sounding in the southern part of seismic profile 2T (Central Slovakia) - BEZÁK, Vladimír; PEK, Josef; MAJCIN, Dušan; BUČOVÁ, Jana; ŠOLTIS, Tomáš; BILČÍK, Dušan; KLANICA, Radek (Contributions to Geophysics and Geodesy, 2015)
In this paper we present a geological interpretation of magnetotelluric sounding along the southern part of the seismic 2T profile situated in the southern Central Slovakia. The complexes with higher conductivity are imaged in the shallow depths, formed by the Tertiary sediments and volcanics. In the northernmost part of the profile, the influence of non-conductive complexes composed of orthogneisses and overlying Mesozoic carbonates is significant. In the central part of the profile, the low conductive granitoid complexes are superposed over the metamorphic rocks with higher conductivity. This structure is a remnant of the Hercynian middle crust nappes. The most outstanding phenomenon of the profile is the sudden, almost step change in the conductivity parameters of the crust in the southern part. The significantly high conductivity of the crust in this area is most probably not related to its lithological composition, but by the abundant supply of fluids in the crust connected with the Neogene tectonic and volcanic processes.